Cuprate addition to a 6-substituted pentafulvene: preparation of sec-alkyl substituted titanocene dichlorides and their biological activity - Cini, Melchior; Bradshaw, Tracey D.; Lewis, William; Woodward, Simon (Wiley-VCH Verlag, 2013)
The copper-catalysed (10 mol-% CuBr·SMe2, CuCN·LiCl or CuI/PPh3) addition of RMgBr to the pentafulvene 1-(cyclopenta-2,4-dien-1-ylidenemethyl)-2-methoxybenzene allows the formation of cyclopentadienyl derivatives with α-CHR(2-MeOPh) sidechains (R = Me, Et, nBu, iBu, allyl, Ph) without H– transfer. The deprotonation of these sec-alkyl-substituted cyclopentadienyls followed by the addition of TiCl4 allows the isolation of TiCl2{η5-C5H4CHR(2-OMePh)} as rac/meso mixtures that show activity against human colon, breast and pancreatic cell lines (GI50 2.3–42.4 μM).